Enhanced electrorheological effectiveness and temperature effect of suspensions based on poly(ionic liquid)s neutralized with mixed counterions. (22nd August 2022) - Dong, Yuezhen; Zhao, Xiaoyang; Peng, Chengshi; Zhao, Ran; Zhang, Yueyue; Zhao, Peiyu; Xu, Xianmang; Yin, Jianbo
Abstract: A series of random co-poly(ionic liquid)s (co-PILs) neutralized with mixed counterions of organic bis(trifluoromethane sulfonyl)imide ([TFSI]) and inorganic tetrafluoroborate ([BF4 ]) of different mole ratio had been synthesized for use as electrorheological (ER) particles. The temperature-modulated ER effect of the co-PIL particles had been investigated and compared with that of homo-poly(ionic liquid)s neutralized with single organic [TFSI] counteranions. This work demonstrated that the ER effectiveness and temperature effect of electrorheological fluid based on neat organic counteranions-typed PILs can be significantly improved by a simple substitution of inorganic counteranions with a suitable mole ratio. The higher electrorheological effectiveness with suppressed leakage current density and enhanced temperature stability originated from that the substitution of inorganic counteranions for organic counteranions could systematically elevate the glass transition temperature and modulate the activation energy of ion movement in PILs matrix. Graphical abstract: Linear polymeric ionic liquids (PILs) neutralized with mixed counteranions of organic ([TFSI]) and inorganic ([BF4 ]) could exhibit higher ER effectiveness and broader working temperatures range than the analogous PILs neutralized with single organic counteranions. Image 1 Highlights: PILs containing organic and inorganic counterions of various mole ratio was prepared for use as electrorheological particles. Partial replacement of [TFSI] by [BF4 ] could improve the electrorheological effectiveness and thermal stability of PILs. Partial replacement of [TFSI] by [BF4 ] could modulate the glass temperature and ionic shifting activation energy of PILs.